PENGARUH LIKUIDITAS, PROFITABILITAS, STRUKTUR ASET, RISIKO BISNIS, DAN DEWAN KOMISARIS TERHADAP STRUKTUR MODAL - indriyani Novitasari; Kartika Hendra Titisar; riana rachmawati Dewi (Jurnal Ilmu Akuntansi, 2020)
Capital structure is the most important part of the company's activities. Source of funds acquired capital structure consists of the source of funds from within the company and outside the company. The capital structure is comparing total debt to capital. The capital structure is measured by DEBT to Equity Ratio (DER). The purpose of this research is to test and analyze the influence of liquidity, profitability, asset structure, business risk, and board of Commissioners on capital structure. The population in this study as much as 10 pharmaceutical companies registered in IDX period 2014-2018. The sample selection technique is purposive sampling. A method used multiple linear regression. Results showed that the liquidity variables, profitability, asset structure, business risk, and Board of Commissioners affected the capital structure. Adjustes R Square value of 0.658. This indicates that a variable variance in the capital structure of 65.8% can be explained by variables, 34.2% explained by factors – other factors outside of the investigation